RANCANG BANGUN ALAT PENGUKUR DISTRIBUSI KUAT PENERANGAN MULTI TITIK MENGGUNAKAN SISTEM KOMUNIKASI RS485 - Indri Trifiantari; Suryono Suryono (Youngster Physics Journal, 2012)
ABSTRACT Meassuring illuminance system was created used multipoint model. The used light sensor was LDR that created used voltage devider model . AVR ATMega8535 microcontroller was used as a data acquisition device and a serial data transmission to a computer. Output of sensor was inserted into the microcontroller ADC input at ADC0 pin. Measured data of the LDR sensor would be processed by AVR ATMega 8535 microcontroller, then sent to a computer using a serial RS485 protocol. The data was interfaced with Borland Delphi7 and saved on Microsoft Excel. From this research, it was found the measurement from 4 terminal systems which each terminal sistem consist of one measurement point. From the four test systems performed by standard luxmeter obtained equipment precision of device that is made between R = 94.84%, until R = 99.05%. Key words: Illumination, LDR, RS485 communication system